Analysis of Factors Affecting Employee Performance with Organizational Commitment as an Intervening Variable in the Rehabilitation Center Work Unit of the Ministry of Defense of the Republic of Indonesia - Herawati, Petty; Hadi Isnanto, Samto (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of organizational culture and work discipline on employee performance with organizational commitment as an intervening variable in the Rehabilitation Center Work Unit of the Ministry of Defense of the Republic of Indonesia (Satker Pusrehap Kemhan RI). The sample in this study was 110 employees, which was determined based on the purposive sampling method with a calculation of 5 times the number of research indicators. Hypothesis testing was carried out using the Partial Least Square (PLS) analysis technique with the help of Smart PLS software. The results of the study showed that organizational culture did not have a significant effect on employee performance, while work discipline had a positive and significant effect on employee performance. In addition, organizational commitment has a positive and significant influence on employee performance, while organizational culture has a positive and significant effect on organizational commitment. Other results also show that work discipline has a positive and significant effect on organizational commitment. These findings indicate that in improving employee performance in the Pusrehap Task Force of the Ministry of Defense of the Republic of Indonesia, work discipline and organizational commitment play a more dominant role compared to organizational culture.